Pengaruh Knowledge Sharing terhadap Organizational Citizenship Behavior dan Work Engagement yang dimediasi oleh Locus of Control - Kumala Putri Ayatullah; Muhammad Irfan Nasution (Mahesa Research Center, 2023)
This article aims to examine the effect of knowledge sharing on organizational citizenship behaviour and work engagement mediated by locus of control among employees of PT. Telkom Gaharu Access. This research focuses in improving the quality of work by the employees with the aim of achieving each organizational goal. The indicators as measuring tools in this study use the theory presented by Afsar, et. al. (2018). The data collected in this study were obtained based on primary data and secondary data with 50 person employees as sample from total population is 150 employees at PT. Telkom Access Gaharu with proportional random sampling method. This research conducted by quantitative method. The findings in this study indicate that in order to increase organizational citizenship and work involvement within an organization which includes quality and performance both for each individual and knowledge sharing is required.